PERANCANGAN VIDEO MUSIK BERJUDUL "SIDE BY SIDE" SEBAGAI MEDIA PROMOSI BAND SLOWRIGHT - Rahman, Augie Bahtiar; Pratama, Bintang Pramudya Putra; Nugroho, Didit Prasetyo (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
The development of the digital music industry has opened up new opportunities for independent musicians like Slowright, a band from Malang with reggae, ska, rap, and hip hop fusion genres, to promote their work. Music videos have become a crucial promotional medium because they can convey the narrative, identity, and aesthetic values of a musical work. Therefore, this research aims to design and produce the "Side by Side" music video for the Slowright band as an effective promotional tool. The method used is descriptive-qualitative with a 5W+1H approach. Data collection was carried out through interviews with band members, observation of music video trends, and documentation of song lyrics and band branding. Data analysis was used to identify visual needs that match the character of the song "Side by Side," understand the band's visual communication style, and recognize the aesthetic preferences of the target audience. The results show that the music video design was successfully implemented, where the main message of the song about loyalty and friendship was visualized with a casual and cinematic concept inspired by 90s hip-hop aesthetics. The production process was carried out at Toko Avia and Eleven Clan Burger in Malang on June 20, 2025. The final music video has a resolution of 4K UHD 3840 x 2160 in H.264 format. This video not only serves as an aesthetic promotional medium but also strengthens the band's image and provides a practical contribution to students.